What to do in /with images? The (virtual) hand in augmented and virtual reality. (AN-ICON. Studies in Environmental Images [ISSN 2785-7433], 2023)
This paper focuses on the concept of acting with and in images in the context of recent AR and VR artworks. The thesis is that the (virtual) hand plays a significant role in an immersive experience. Referring to Doris Kolesch’s relational concept of immersion as one that considers not only the status of being evolved but also the process of getting inside, three forms of actions in and with images are discussed: the hand as stage, the hand as a symbiotic contact zone, and the hand as a designing hand. With artworks by Jeremy Bailey, Aristarkh Chernyshev, Rachel Rossin, and Florian Meisenberg, this contribution aims to contour the forms of action in which the (virtual) hand, in particular, allows an immersive experience by interaction with the virtual sphere and knows how to combine distance with nearness.
Keywords: Immersive experience; Virtual reality; Augmented reality; Virtual hand; Contemporary art